Discovery of a novel class of pyridine derivatives that selectively inhibits mutant isocitrate dehydrogenase 2. (30th March 2018) - Wang, Fangying; Li, Zhuoling; Zhang, Tao; Yan, Guoyi; Hu, Mingxing; Zhao, Lifeng; Zhao, Yinglan; Chen, Yuanwei
Abstract : This paper presents synthesis and structure–activity relationship of pyridine derivatives as inhibitors of mutant isocitrate dehydrogenase 2 (IDH2). A series of 2, 4, 6‐trisubstituted pyridine derivatives have been prepared and evaluated in vitro. Among these compounds, 14n exhibited excellent inhibition activity with the IC50 of 54.6 nm, which is approximately onefold improvement compared to drug candidate AG‐221 (Enasidenib) that is in Phase III trial. Exquisite selectivity of14n for IDH2 R140Q mutant isoform was demonstrated by the poor activity against the wild‐type IDH1 and IDH2. Abstract : Thirty‐six 2, 4, 6‐trisubstituted pyridine derivatives have been prepared and evaluated in vitro. Among these compounds, 14n exhibited excellent inhibition activity with the IC50 of 54.6 nm, which is approximately onefold improvement compared to drug candidate AG‐221 (Enasidenib) that is in Phase III trial.